Governance and Profitability in Value of Family Companies in the Manufacturing Sector - utami, Pande Rahayu Trisna; Christianti, Ari (Jurnal Bisnis dan Manajemen, 2023)
The general purpose of the companies are to increase their value. The value is important because it reflects investors' perceptions of the company's performance. This study aims to examine the effect of the size of the board of directors, the size of the audit committee, and ROA (Return on Assets) on Tobin's Q. The sample used in this research is family companies that categorize in the Manufacturing sectoral from 2015-2019. The results showed that profitability had a positive effect on firm value. However, the size of the board of directors has a negative effect on firm value. It is possible that a smaller board of directors may be more active in coordinating and communicating than a larger number of directors. In addition, a more limited number of directors can improve company performance because consensus in decision making and communication becomes more effective.